The Comparison of Language Learning Strategies between Iranian and Iraqi EFL Learners Based on 1990 Oxford's Model - Azadeh Nemati; Abdullah Griei (Universitas Islam Negeri Walisongo Semarang, 2022)
The present study investigates the comparison of language learning strategies between Iraqi and Iranian EFL learners based on Oxford's model. To accomplish this, 60 BA-level participants—30 Iraqi and 30 Iranian EFL learners—from the Public University in Babylon, Iraq, and the Islamic Azad University in Shiraz, Iran—were given the 5-point Likert scale of 50 questions from Oxford's Strategies Inventory of Language Learning (SILL). They were between the ages of nineteen and twenty-eight. This quantitative and survey study used frequencies, means, standard deviations, and t-scores to quantify the dimensions of language learning strategies (LLS) and compare LLS between Iranian and Iraqi EFL learners. According to descriptive data, all LLSs among Iraqi EFL learners fell into the medium range. However, Iranian EFL students exhibited metacognitive and memory strategies more frequently and moderately. The results also distinguished Iranian and Iraqi EFL students' language learning approaches. According to the study, Iranian learners used different English learning strategies than Iraqi students. To this end, this research can also serve as a reference in language learning strategies and specify the dimensions of LLS used by Iraqi and Iranian EFL learners. The important implication of this research is that if EFL learners and teachers get aware of language learning strategies, they may develop their learning and teaching more easily and successfully.